On H-irregular reflexive labeling of graph - Marsidi, Marsidi; Agustin, Ika Hesti; Dafik, Dafik; Rahman, Md. Saidur; Sullystiawati, Lusia Herni (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2023)
By an irregular reflexive  labeling, we mean a function  and  such that  if  and  if , where  max . Let , the irregular reflexive  labeling is called an -irregular reflexive -labeling of graph  if every two different sub graphs  and  isomorphic to , it holds , where . The minimum  for graph  which has an -irregular reflexive -labeling is called the reflexive  strength of graph and denoted by . In this paper we initiate to study the lower bound of the reflexive  strenght of graphs and the reflexive  strenght of flower, Shack  and book graph, where  isomorphic to and , respectively.